Strategi Dinas Koperasi dan UKM Kota Bandar Lampung Dalam Meningkatkan Kegiatan Usaha Pelaku Usaha Mikro Kecil dan Menengah (UMKM) Pasca Pandemi Covid-19 - Tini Maharani; Nana Mulyana; Vina Karmilsari (Jurnal Administrativa, 2023)
The impact of the Covid-19 pandemic which has resulted in a decline in business activities in various sectors, one of which is the UMKM sector in the city of Bandar Lampung, where the UMKM sector plays an important role in economic progress in the city of Bandar Lampung. Therefore, an effective strategy is needed to overcome these problems. This study aims to determine the strategy of the Bandar Lampung City Cooperatives and UKM Office in increasing the business activities of UMKM actors after the Covid-19 pandemic, based on the strategic theory indicators by Richard P Remuld which there are 3 indicators, namely Diagnosis, Guiding Policies, and Coherent Actions by adjusting with the conditions at the Department of Cooperatives and UKM in Bandar Lampung and UMKM business actors. The method used is the technique of collecting data from observations, interviews, and documentation. The results showed that by paying attention to the research indicators there were obstacles regarding budget funds that made various activities not realized. Therefore the Department of Cooperatives and UKM Bandar Lampung has prepared strategies such as carrying out socialization activities, training, making capital assistance programs for UMKM business actors, as well as providing a forum for UMKM business actors to carry out their business activities.